The Significance of Angiotensin-Converting Enzyme-2 (ACE2) in SARSCov- 2 Infection and COVID-19 - Restini, Carolina; Belavek, Trevor; Bernal, Rafael; Ibrahim, Vanessa; Irwin, Kelly; Kim, Minjung; Merlo, Courtney (Coronaviruses, 2021)
The new coronavirus was first reported in 2019 (China) and officially announced by the World Health Organization as a pandemic in March 2020. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of the pneumonia-associated illnesses and shares structural homology with the related Severe acute respiratory syndrome coronavirus-1 (SARS-CoV- -1). One of the mechanisms for SARS-Cov-1 and -2 infection is mediated by the angiotensin-converting enzyme-2 (ACE2) cell receptor, enabling the virus to enter the host cells. ACE2 is an isoform of the angiotensin-converting enzyme 1 (ACE). The actions of ACE2 counterbalance the classic renin-angiotensin system (RAS) axis through the production of Ang 1-7, which promotes cardiovascular, renal, and lung-protective effects. The ACE2 is not the only route for SARS-CoV-2 to enter the host cells. However, due to its roles in the RAS and its participation in the SARS-CoV-2 virulence, ACE2 has gained attention regarding viral mechanisms of pathogenesis, effects of drugs that interfere with the RAS, and as a potential target for therapeutic strategies for the damages caused by SARS-CoV-2 infection. Among other tissues, ACE2 gene expression seems to be increased in the lungs upon SARS-CoV-2 infection; however, amid other variables, expression and/or activity of ACE2 is shown as a disease, sex, and age-dependent. The present review covers critical aspects for a comprehensive understanding of ACE2 and its current involvement in SARSCoV- 2 infection and the development of COVID-19.
Keywords: angiotensin-converting enzyme- 2 (ACE2)